2013
DOI: 10.1002/jcp.24418
|View full text |Cite
|
Sign up to set email alerts
|

A role for the chemokine receptor CCR6 in mammalian sperm motility and chemotaxis

Abstract: Although recent evidence indicates that several chemokines and defensins, well-known as inflammatory mediators, are expressed in the male and female reproductive tracts, the location and functional significance of chemokine networks in sperm physiology and sperm reproductive tract interactions are poorly understood. To address this deficiency in our knowledge, we examined the expression and function in sperm of CCR6, a receptor common to several chemoattractant peptides, and screened several reproductive tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 85 publications
1
55
2
1
Order By: Relevance
“…sea urchins and starfish) and have been shown to alter sperm behaviour [65,66]. Recent research in mammals has also identified several chemokines present in human follicular endometrial fluid that interact with a receptor common to several chemoattractant peptides present in mouse and human sperm-peptides that modify sperm velocity and chemotaxis [67]. Table 2.…”
Section: Discussion (A) Evidence For Cryptic Female Choicementioning
confidence: 99%
“…sea urchins and starfish) and have been shown to alter sperm behaviour [65,66]. Recent research in mammals has also identified several chemokines present in human follicular endometrial fluid that interact with a receptor common to several chemoattractant peptides present in mouse and human sperm-peptides that modify sperm velocity and chemotaxis [67]. Table 2.…”
Section: Discussion (A) Evidence For Cryptic Female Choicementioning
confidence: 99%
“…In the context of this review, it is of specific interest that fewer than 30% of live human spermatozoa express chemokine CXC motif receptor 4 [98,99], meaning that approximately 70% of spermatozoa would be unresponsive to chemical signals emanating from granulosa cells and oocytes. The other study [97] identified CCR6, a chemokine receptor common to several chemoattractant peptides in human and mouse spermatozoa, and also noted that the protein was not detected in every cell. Interactions between chemokine receptors and one specific b-defensin (DEFB126), which is distributed along the human sperm surface [100,101] and mediates spermoviduct attachment in macaques [102], have recently also been implicated for their importance in the progression of spermatozoa through viscous media.…”
Section: Can the Oviduct Distinguish The Genetic Properties Of Spermamentioning
confidence: 93%
“…Progesterone elicits its effects via its receptor, CatSper [94][95][96], and the consequent modulation of intracellular calcium concentrations changes flagellar activity. In addition, two recent studies [97,98] have found that sperm chemotaxis is modulated not only by progesterone but also via chemokine-receptor interactions involving factors produced by oocytes, granulosa cells, and endometrial cells. One of the studies [98] focused on the interaction between chemokine CXC motif receptor 4 present in human spermatozoa and chemokine stromal cellderived factor 1, a member of the CXC chemokine family also known as CXCL12.…”
Section: Can the Oviduct Distinguish The Genetic Properties Of Spermamentioning
confidence: 96%
“…In humans, freshly released cumulus-oocyte complexes (COCs) can secrete progesterone (P 4 ) as a chemoattractant for sperm (Teves et al 2006, Oren-Benaroya et al 2008. Chemokine receptors -CCR1, CCR5 and CCR6 -have been identified on human sperm (Isobe et al 2002, Caballero-Campo et al 2014. CCL20 ligands found in the follicular fluid can bind to CCR6 and alter sperm directional movement (Caballero-Campo et al 2014).…”
Section: Chemotaxismentioning
confidence: 99%
“…Chemokine receptors -CCR1, CCR5 and CCR6 -have been identified on human sperm (Isobe et al 2002, Caballero-Campo et al 2014. CCL20 ligands found in the follicular fluid can bind to CCR6 and alter sperm directional movement (Caballero-Campo et al 2014). The merging of follicular fluid and the oviductal fluid after ovulation may provide sufficient chemoattractants to ensure the arrival of sperm at the ampulla.…”
Section: Chemotaxismentioning
confidence: 99%